2021
DOI: 10.5664/jcsm.9326
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of central disorders of hypersomnolence: an American Academy of Sleep Medicine systematic review, meta-analysis, and GRADE assessment

Abstract: Introduction: This systematic review provides supporting evidence for the accompanying clinical practice guideline on the treatment of central disorders of hypersomnolence in adults and children. The review focuses on prescription medications with U.S. Food & Drug Administration approval and nonpharmacologic interventions studied for the treatment of symptoms caused by central disorders of hypersomnolence. Methods: The American Academy of Sleep Medicine commissioned a task force of experts in sleep medicine to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 110 publications
(362 reference statements)
2
12
0
Order By: Relevance
“…In contrast, in the 2002 twice-nightly SXB pivotal clinical trial, only the 9-g dose was statistically significant on EDS as measured by the ESS [ 33 ]. Newly released clinical practice guidelines from the American Academy of Sleep Medicine set a change from baseline compared to placebo of two or more minutes on the MWT, including the 95% CIs, as being the clinical significance threshold [ 34 , 35 ]; ON-SXB achieved this standard for all three doses evaluated ( Figure 3A ). This is the first randomized controlled trial that demonstrated the efficacy and safety of a 7.5-g dose of SXB; given that the efficacy was nearly comparable to the 9-g dose compared to placebo, this may afford confidence for clinicians and patients that a lower dose can be effectively used in practice.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the 2002 twice-nightly SXB pivotal clinical trial, only the 9-g dose was statistically significant on EDS as measured by the ESS [ 33 ]. Newly released clinical practice guidelines from the American Academy of Sleep Medicine set a change from baseline compared to placebo of two or more minutes on the MWT, including the 95% CIs, as being the clinical significance threshold [ 34 , 35 ]; ON-SXB achieved this standard for all three doses evaluated ( Figure 3A ). This is the first randomized controlled trial that demonstrated the efficacy and safety of a 7.5-g dose of SXB; given that the efficacy was nearly comparable to the 9-g dose compared to placebo, this may afford confidence for clinicians and patients that a lower dose can be effectively used in practice.…”
Section: Discussionmentioning
confidence: 99%
“…A clinically meaningful response in cataplexy, defined as a reduction in WRC of at least 50%, was noted in 61% of pitolisant-treated patients at the last on-treatment assessment in HARMONY CTP; 76% of patients had a WRC reduction of at least 25%. The definitions of clinically meaningful response used in this analysis are consistent with clinical significance thresholds identified in the systematic literature review that supported the 2021 American Academy of Sleep Medicine clinical practice guideline on the treatment of central disorders of hypersomnolence [ 39 ].…”
Section: Discussionmentioning
confidence: 90%
“…At week 1, the mean ESS and IHSS scores decreased from baseline by 2.3 and 4.4 points, respectively, which is consistent with the established thresholds for a minimum within-person change (≥2 points for ESS [based on narcolepsy] and 4 points for IHSS [IH specific]). 16,21 Improvements in scores of the QoL measures FOSQ-10 and WPAI:SHP were also observed at the end of stable-dose treatment. Participants reached a stable dose of LXB in a median of 48.5 days; the median dose was 7 g/night, and the majority of participants were stable on a twice-nightly dosing regimen.…”
Section: Discussionmentioning
confidence: 94%